2005
DOI: 10.5194/angeo-23-1433-2005
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion properties of ducted whistlers, generated by lightning discharge

Abstract: Abstract. Whistler-mode wave propagation in magnetospheric ducts of enhanced cold plasma density is studied. The case of the arbitrary ratio of the duct radius to the whistler wavelength is considered, where the ray-tracing method is not applicable. The set of duct eigenmodes and their spatial structure are analysed and dependencies of eigenmode propagation properties on the duct characteristics are studied. Special attention is paid to the analysis of the group delay time of one-hop propagation of the whistle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In spite of this long history, terrestrial whistlers still attract active research, for example in connection with lightning‐induced precipitation of energetic electrons [ Peter and Inan , 2004, 2007; Bortnik et al , 2006; Inan et al , 2007], with propagation of whistlers in magnetospheric density structures and ducts [ McCormick et al , 2002; Platino et al , 2005; Pasmanik and Trakhtengerts , 2005], with loss processes in the Van Allen radiation belts [ Bortnik et al , 2003; Rodger et al , 2003], with the dynamics of the slot region [ Meredith et al , 2007], and with the still controversial question of the origin of plasmaspheric hiss [ Sonwalkar and Inan , 1989; Draganov et al , 1992; Green et al , 2005, 2006; Thorne et al , 2006; Bortnik et al , 2008].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this long history, terrestrial whistlers still attract active research, for example in connection with lightning‐induced precipitation of energetic electrons [ Peter and Inan , 2004, 2007; Bortnik et al , 2006; Inan et al , 2007], with propagation of whistlers in magnetospheric density structures and ducts [ McCormick et al , 2002; Platino et al , 2005; Pasmanik and Trakhtengerts , 2005], with loss processes in the Van Allen radiation belts [ Bortnik et al , 2003; Rodger et al , 2003], with the dynamics of the slot region [ Meredith et al , 2007], and with the still controversial question of the origin of plasmaspheric hiss [ Sonwalkar and Inan , 1989; Draganov et al , 1992; Green et al , 2005, 2006; Thorne et al , 2006; Bortnik et al , 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The ray tracing method is applicable when the duct radius is greater than the characteristic wave-length (Strangeways, 1999). Pasmanik and Trakhtengerts (2005) have studied whistler mode wave propagation in magnetospheric ducts of enhanced cold plasma density for the arbitrary ratio of the duct radius to the whistler wavelength (where the ray tracing method is not applicable). They have showed that in the case of the source exciting simultaneously several duct eigenmodes, the receiver should register the set of discrete signals each corresponding to one of the excited eigenmodes.…”
Section: Ducted Mode Of Propagationmentioning
confidence: 99%
“…Theoretical aspects of the whistler wave propagation in the magnetospheric ducts have been studied for more than half a century using different approaches (see, e.g., (Karpman and Kaufman, 1984;Laids, 1992;Pasmanik and Trakhtengerts, 2005;Sonwalkar, 2006;Woodroffe et al, 2013)). Known experimental data make it possible to define concretely the important characteristics of the geophysical situation.…”
Section: Introductionmentioning
confidence: 99%